PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK BERBASIS KOMIK BERSERI TERHADAP MINAT BACA SISWA KELAS IV DI MIN KOTA MEDAN - Rora Rizky Wandini; Emeliya Sukmadara Damanik; Nirwana Anas (PIONIR: JURNAL PENDIDIKAN, 2022)
This comic design aims to determine students' interest in reading related to thematic learning during the pandemic. This research was developed using the Brog & Gal model which was simplified into 5 stages, namely: researchers collecting data, product analysis developed, developing initial products, expert validation and design and revision, small field trials and product revisions, large scale field trials and the final product. Taking questionnaires, interviews, data were analyzed using descriptive analytic is data collection. The results of this study are thematic learning media based on comic series are declared valid with a very feasible category with a percentage of 97.83%. It was declared practical with a percentage of 76.49% in the very practical category, and effective with a percentage of 79.56%.